QUEERING CYC PRAXIS: WHAT I LEARNED FROM LGBTQI+ NEWCOMER, REFUGEE, AND IMMIGRANT STUDENT EXPERIENCES IN CANADA - Marshall, Nancy (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
This exploratory autoethnographic study, undertaken by a White straight cisgender child and youth care practitioner, seeks to understand the experiences of LGBTQI+ newcomer, refugee, and immigrant students in Canada. It highlights the nuances of creating safe spaces for young people who experience harm due to the intersections of systemic racism, xenophobia, transphobia, and homophobia. The overarching finding of this study reveals a culture of silence. Queer newcomer, refugee, and immigrant youth in Canada are often reluctant to disclose or explore their queerness due to their fears of discrimination and violence. This fear exists notwithstanding the pride Canada takes in its efforts to protect LGBTQI+ rights. Inspired by findings from interviews with two women, one who supports LGBTQI+ newcomers, refugees, and immigrants to Canada, and one who researches policy affecting all Canadian refugee experiences, I utilized a self-reflexive deep-dive approach to learn about the events and policies that have shaped LGBTQI+ newcomer, refugee, and immigrant students’ access to postsecondary education in Canada. Central findings in this study point to barriers emerging from homonationalism, colonization, religion, culture, race, White-centred gay–straight alliances in schools, and immigration policies pertaining to sexual orientation and gender identity expression (SOGIE). These findings problematize the White, Westernized, liberal, out-and-proud policies that child and youth care practitioners are accustomed to.